Basis of subsidy of tax on gasoline, a poor collection (2016)
The thrust given to counties with minor incomes, by the Fondo de subsidio de sobretasa a la gasolina in order for them to finance their infrastructure projects, is very important as it is a mechanism that allows these counties to build roads, bridges, docks, etc. These structures help the habitants of the counties to move around the territory and commercialize their products. This produces sources for their maintenance, invigorates economy, creates new work positions and connectivity with the rest of the country so that these particular regions can access to health care systems, technology, communication and further systems that encourage development in these territories. These are the reasons why it is very important to give the counties all the support and guarantee that they receive the sources from the Fondo de Subsidio de Sobretasa a la Gasolina. This should be done by appealing to legal instances, creating controlling politics and surveillance to avoid that the entities in charge of managing this resources do not have the opportunity to retain them illegally by surpassing the norms that establish and regulate their administration.